2018
DOI: 10.3389/fnins.2018.00930
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metabolic Syndrome on Neuroinflammation and the Blood–Brain Barrier

Abstract: Metabolic syndrome, which includes diabetes and obesity, is one of the most widespread medical conditions. It induces systemic inflammation, causing far reaching effects on the body that are still being uncovered. Neuropathologies triggered by metabolic syndrome often result from increased permeability of the blood–brain-barrier (BBB). The BBB, a system designed to restrict entry of toxins, immune cells, and pathogens to the brain, is vital for proper neuronal function. Local and systemic inflammation induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
183
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(191 citation statements)
references
References 250 publications
(345 reference statements)
2
183
1
5
Order By: Relevance
“…FOXO1 regulates vascular endothelial growth factor A (VEGFA) expression and promotes angiogenesis in healing wounds (28). Under inflammatory conditions, VEGF increases vascular permeability (29), an effect mediated by cldn5 disruption (30). It will be interesting to further evaluate endothelial cell signaling in prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO1 regulates vascular endothelial growth factor A (VEGFA) expression and promotes angiogenesis in healing wounds (28). Under inflammatory conditions, VEGF increases vascular permeability (29), an effect mediated by cldn5 disruption (30). It will be interesting to further evaluate endothelial cell signaling in prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…One energetically favorable miRNA-146a and/or miRNA-155 mRNA target, both confirmed by bioinformatics and miRNA-mRNA-3'-UTR binding luciferase-reporter assay, is the 3'-untranslated region (3'-UTR) of complement factor H (CFH) mRNA resulting in, respectively, the down-regulation of CFH expression [26,27,48,87]. A down-regulated CFH is associated with the disruption of innate-immune signaling that supports inflammatory neurodegeneration and amyloidogenesis [17,34,36,45,55,75,[89][90][91]. Although CFH is easily detected in the brain parenchyma and neuronal cytoplasm it is also highly abundant in the blood serum of the human systemic circulation, as may be some other pathogenic blood-cell-based biomarkers that may include specific kinase mutations and other polymorphisms [17,45,55,68,91; see also https://www.sigmaaldrich.com/catalog/product/sigma/c5813?lang=en&region=US; ENSG000 00000971-CFH/ tissue; last accessed 4 July 2019].…”
Section: Up-regulated Micrornas (Mirnas) and Down-regulation Of Essenmentioning
confidence: 99%
“…Importantly, CFH has several structurally related proteins also encoded at the regulator of complement activation gene cluster at human chromosome 1q31.3 that lack relevant complement regulatory activity -these are known as CFH-related (CFHR) proteins [36,53,55]. The balance between the actions of CFH and the CFHR proteins: (i) determines the degree of complement activation and the innate-immune response; and (ii) regulates the neurophysiological roles of CFH and CFHR in CNS health and disease [36,75]. The functional contributions of CFH and CFHR-mediated signaling to the innate-immune response in inflammatory neurodegeneration are currently not completely understood [36,55,75].…”
Section: Up-regulated Micrornas (Mirnas) and Down-regulation Of Essenmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate CNS involvement with ALL (CNS 2) in the setting of obesity may be due to technical difficulty during a diagnostic lumbar puncture (ie obtaining peripheral blood elements in the sample), the biologic gradient seen in our study (though not statistically significant due to the limited number of CNS positive cases) suggests this finding is real and not purely due to technique. Additionally, other studies have shown obesity can impact neuro-inflammation and the permeability of the blood brain barrier [44][45][46][47] suggesting a biological mechanism for ALL penetration into the CNS in patients who are obese.…”
Section: Discussionmentioning
confidence: 99%